Pengaruh Penambahan Monoetanolamin (MEA) pada Sifat Listrik dari Material Copper Tin Oxide - Faizah, Suci Hanim; Sanjaya, Hary; Budiman, Septian (Lembaga Yasin AlSys, 2024)
Semiconductors are materials with interesting electrical properties. Copper tin oxide (CuSnO3) is an oxide semiconductor material with a band gap value of 2.0-2.5 eV. The method used is sol-gel method with the addition of monoethanolamine (MEA). Copper (II) nitrate trihydrate and tin (II) chloride dihydrate as precursors and methanol as solvent. The purpose of this research is to see the effect of MEA addition on the electrical properties of CuSnO3. Characterization results using UV-DRS showed the band gap of CuSnO3 obtained with the addition of 1.5 mL of MEA was 1.71 eV and without the addition of MEA was 2.36 eV. The addition of MEA can reduce the band gap value. Electrical conductivity will be better with the smaller band gap value.